Preparation, Characteristics, and Application of Biopolymer Materials Reinforced with Lignocellulosic Fibres - S. V. Gurupranes; I. Rajendran; S. Gokulkumar; M. Aravindh; S. Sathish; Md. Elias Uddin (International Journal of Polymer Science)
Various environmental concerns motivate scientists and researchers to look out for unique new materials in science and technology. In order to address the demand for polymeric materials with partial biodegradability, the usage of lignocellulosic fibre in the polymer matrix has risen. Lignocellulosic fibres are a cheap, easily renewable resource that is readily available in all regions. Cellulosic plant fibres also have a plethora of possibilities for use in polymer reinforcement because of their properties. Many researchers put their effort into developing a natural polymer with better mechanical properties and thermal stability using nanotechnology and the use of natural polymers to make its composites with lignocellulosic fibres. This study provides a review of the biodegradable composite market, processing methods, matrix-reinforcement phases, morphology, and characteristic improvements. In addition, it provides a concise summary of the findings of significant research on natural fibre polymer composites (NFRCs) that have been published. Indeed, a noticeably brief discussion is provided on the significant issues faced during composite extraction as well as the challenges encountered during the machining. Recent developments in the study of lignocellulosic fibre composites or NFRCs have demonstrated their enormous potential as structural elements in vehicles, aerospace structures, buildings, ballistics, soundproofing, and other structures.